(untitled) (Biological Sciences - PJSIR, 1995)
Two hydrazones were subjected to study. The first hydrazone was the p-dimethylaminobenzalde- hyde-benzoylhydrazone (DMB). This hydrazone was used to determine Cu2+ by spectrophotometric method. This method depends on the extraction of Cu-DMB complex in chloroform. Maximum absorption was attained at 440 nm at pH 7-10. The second hydrazone, p-dimethylaminobenzaldehyde-p-nitrophenylhydrazone (DMN) was tested as an acid-base indicator. DMN compound was studiedin UV andvisible regions atdifferent pH-values. DMN compound was found to have two pK, values, 3.31 and 9.1. DMN was tested as acid-base indicator. It gave satisfied results for (1) strong acid-strong base system (2) strong acid-weakbase system (3) weak acid-strong base system.The result was found to have maximum error 2% with maximum standard deviation 1.59.